(3JSgjd GdJSWjM GdCSWQdGHi hGdYed HeQcHGJ GdTeGdi hGdLfhHi efgs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3eMeO Hf CHj GdWjH GdQUOi s)
(3ChdgG (B:s
(3cJHJ gfG cd eG NWQ HGdHGd, hJUhQ ai GdhbJ hGdMGd ef CYeGd JSWjM GdcQI hJUhjQgG HeG Cecf ef CfhGY GdUhQ , MJi XffJ , Ch Xf , Cfi ESJhYHJ eG jecf Cf jJhge ajg s
(3BNQgG (B:s
(3EfbSGe GdHQhL ajg HGdOQL hGdObGFb eY UZQ bdH GdCSWQdGH agPg gi CUfGa GdCSWQdGHGJ GdJi PcQfGgG ai Pdc GdcJGH hehdGi jcJai ef GdcKjQ HGdbdjd , hjcai HPcGFg ageg eDhfg GdcKjQ GdWhjd hJe GdcJGH HCSQg s
(3HgG HYV GdCTcGds
(3hgh SDGdGf hCQHYI YTQ bhdkGs
(3cJHJ Hbde eged GdfbW cKjQkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs